Isobaric vapor-liquid equilibria for the extractive distillation of 2-propanol + water mixtures using 1-ethyl-3-methylimidazolium dicyanamide ionic liquid. (July 2017) - Orchillés, A. Vicent; Miguel, Pablo J.; González-Alfaro, Vicenta; Llopis, Francisco J.; Vercher, Ernesto; Martínez-Andreu, Antoni
Graphical abstract: Highlights: VLE of binary and ternary systems of 2-propanol, water and [emim][DCA] at 100 kPa. The e-NRTL model fits the VLE data of 2-propanol + water + [emim][DCA] system. [emim][DCA] breaks the 2-propanol + water azeotrope at an IL mole fraction >0.085. Abstract: Isobaric vapor–liquid equilibria for the binary systems 2-propanol + water, 2-propanol + 1-ethyl-3-methylimidazolium dicyanamide ([emim][DCA]), and water + [emim][DCA] as well as the vapor–liquid equilibria for the 2-propanol + water + [emim][DCA] ternary system have been obtained at 100 kPa using a recirculating still. The electrolyte nonrandom two-liquid (e-NRTL) model was used for fitting successfully the experimental data. The effect of [emim][DCA] on the 2-propanol + water system has been compared with that produced by other ionic liquids reported in the literature. From the results, [emim][DCA] appears as a good entrainer for the extractive distillation of this solvent mixture, causing the azeotrope to disappear at 100 kPa when the ionic liquid mole fraction is greater than 0.085.